2021
DOI: 10.3389/fmars.2021.740130
|View full text |Cite
|
Sign up to set email alerts
|

Summer Phytoplankton Blooms Induced by Upwelling in the Western South China Sea

Abstract: During summer, phytoplankton blooms occur frequently off the southeast Vietnam coast in the western South China Sea (WSCS). Using multi-source remote sensing data, such as sea surface temperature (SST), sea surface wind (SSW), aerosol optical thickness (AOT), sea level anomalies (SLA), and chlorophyll-a (Chl-a) data from 1998 to 2020 and in situ observations of analyzed data, we report the patterns of spatial variation of summer phytoplankton blooms in this region. The partial correlation and multiple stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
1
5
1
Order By: Relevance
“…This pattern is consistent with the result of the dome tracing result in which the dome is developed on the lee side of Sri Lanka, to the northwest of the SMC [46]. The counterclockwise pattern of the geostrophic current is consistent with the negative SSHA that usually favors upwelling in the coastal ocean [47][48][49]. However, the summer high chlorophyll patch does not match the negative SSHA region.…”
Section: Sea Surface Heightsupporting
confidence: 82%
“…This pattern is consistent with the result of the dome tracing result in which the dome is developed on the lee side of Sri Lanka, to the northwest of the SMC [46]. The counterclockwise pattern of the geostrophic current is consistent with the negative SSHA that usually favors upwelling in the coastal ocean [47][48][49]. However, the summer high chlorophyll patch does not match the negative SSHA region.…”
Section: Sea Surface Heightsupporting
confidence: 82%
“…Conversely, the GAM analyses indicated that in contrast to diet, the temperature was not significantly correlated with the distribution of medusae (Table 3 and Figure 6). The nutrientrich coastal water was carried into the WJR, causing higher phytoplankton density in the WJR than that in adjacent waters (Liu et al, 2012;Lu et al, 2018;Chen et al, 2021) and supporting high zooplankton biomass (Thibault et al, 1994). As a carnivorous predator with a broad zooplanktivorous diet (Pavez et al, 2010;Haberlin et al, 2019), the abundance of medusae increases due to the elevated chlorophyll concentration and zooplankton biomass in the WJR (Coyle and Cooney, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The cold coastal water is transported to the open SCS under the combined influence of the southwest wind jet and southern anticyclonic gyre, forming a clear cold filament in the sea surface temperature (Li et al, 2017;Huang et al, 2020;Sun and Lan, 2021). Generally, the cold coastal water could spread eastward over most of the central SCS (approximately 115 • E) in summer (Xie et al, 2003;Chen et al, 2021). The complex physical dynamic processes of the wind jet in the midwestern SCS attracted a lot of attention (Ning et al, 2004;Liu et al, 2012;Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data uses the Garver-Siegel-Maritorena semi-analytical ocean color algorithm [ 25 ]. The Chl- a data have been widely used to study the distribution characteristics of phytoplankton Chl- a in the South China Sea [ 26 ]. Considering the large number of clouds in the study area and many gaps in the daily data, this study selects data with a temporal resolution of 8-day averaged and a horizontal resolution of (0.04° × 0.04°) from the merged daily Chl- a product.…”
Section: Methodsmentioning
confidence: 99%